Merekonstruksi Makna Islam sebagai Agama Perdamaian - Sofwan Jannah (Unisia, 2004)
Islam actually religion of peace which provided by Allah as guidance for life and worshiping Allah, but recently, Islam's face more likely shown as a terrorist, an image that actually far away beyond it's original meaning. Syariat Islam brings guidance to success in this worldly life and eternal life in hereafter, which is known as rahmatan lil 'alamin, it means, Islam, for everyone, even for disbelievers, can live side by side peacefully as long as they respect and uphold each other. Only the power which causes destruction must be taken account as an enemy.